A cost-effective voice coil motor-based portable micro-indentation device for in situ testing. (1st December 2020) - Peng, Guangjian; Xu, Fenglei; Chen, Jianfeng; Hu, Yahao; Wang, Huadong; Zhang, Taihua
Highlights: A portable micro-indentation device was developed. Design principle of indentation device was discussed. A new method to calculate indentation force was proposed. The equivalent model of developed device was analyzed. The device can measure elastic modulus and hardness with acceptable accuracy. Abstract: To evaluate the mechanical properties of structures in service, a portable micro-indentation device was developed and built. The basic design principle of the indentation device, i.e. measurement of the indentation depth and the indentation force with sufficient accuracy, was discussed. To avoid using load cell to decrease the machine compliance, a new method that using the current through voice coil motor to calculate the indentation force was proposed. After analyzing the equivalent mechanical model of the developed device, an eddy current displacement sensor was installed on the device to improve the measurement accuracy of indentation depth. Indentation tests were performed on polymethylmethacrylate (PMMA) and unplasticized polyvinyl chloride (UPVC) with the developed device and the commercial indentation device ZHU2.5 to demonstrate the validity and accuracy of the developed micro-indentation device.